Media and Elderly: The Role of Media in Handling Post Retirement Syndrome - Aziz, Rifqi Abdul; Pramana, Pramana; Setianingrum, Vinda Maya; Purwati, Eli (Jurnal The Messenger, 2025)
Purpose: This research investigates how media--especially social media and artificial intelligence (AI)--help older adults overcome psychological and social challenges associated with Post Retirement Syndrome. It aims to understand how digital platforms address communication difficulties in retirement. By examining media usage and AI-assisted interactions, the study explores how technology enhances emotional well-being and promotes social integration in the post-retirement phase of life. Methods: This research employed a qualitative method to analyze the media behavior of retirees through interviews and field observations. Older adults in Bandung were selected using a maximum variation sampling strategy to reflect diverse occupational backgrounds. Bandung was chosen due to its demographic makeup, which includes a growing population of retirees with varying levels of digital engagement, making it an ideal setting to examine the relationship between media use, aging, and retirement experiences. Findings: The findings indicate that social media--particularly Facebook and WhatsApp--has become a transformative tool in addressing Post-Retirement Syndrome. These platforms help older adults maintain social connections, share experiences, and engage with supportive communities. With the help of AI, seniors can more effectively identify and interact with relevant groups, tailoring digital experiences to personal needs and fostering meaningful relationships. Originality: Although much research focuses on interpersonal communication in the elderly, few studies explore how media and AI act as bridges for retirees to reconstruct self-concept and build resilience through social media.